Efficacy of Whole-Body Electromyostimulation (WB-EMS) on Body Composition and Muscle Strength in Non-athletic Adults. A Systematic Review and Meta-Analysis - Kemmler, Wolfgang; Shojaa, Mahdieh; Steele, James; Berger, Joshua; Fröhlich, Michael; Schoene, Daniel; von Stengel, Simon; Kleinöder, Heinz; Kohl, Matthias (Frontiers in Physiology, 2021)
This systematic review and meta-analysis set out to determine the efficacy on whole-body electromyostimulation (WB-EMS) on body composition and strength parameters in non-athletic cohorts. A systematic review of the literature according to the PRISMA statement included (a) controlled trials, (b) WB-EMS trials with at least one exercise and one control group, (c) WB-EMS as primary physical intervention, (d) WB-EMS with at least six electrodes covering most muscle groups, (e) non-athletic cohorts. We searched eight electronic databases up to June 30th 2020 without language restrictions. Standardized mean differences (SMD) for muscle mass parameters, total body fat mass, maximum leg extension and trunk extension strength were defined as outcome measures. In summary, 16 studies with 19 individual WB-EMS groups representing 897 participants were included. Studies vary considerably with respect to age, BMI, and physical conditions. Impulse protocols of the studies were roughly comparable, but training frequency (1-5 sessions/week) and intervention length (6–54 weeks) differ between the studies. SMD average was 1.23 (95%-CI: 0.71-1.76) for muscle mass, 0.98 (0.74-1.22) for maximum leg and 1.08 (0.78-1.39) for maximum trunk extension strength changes (all p<.001). SMD for body fat changes (-0.40, [-0.98 to 0.17]), however did not reach significance. I2 and Q-statistics revealed substantial heterogeneity of muscle- and fat mass changes between the trials. However, rank and regression tests did not indicate positive evidence for small-study bias and funnel plot asymmetries. This work provided further evidence for significant, large-sized effects of WB-EMS on muscle mass and strength parameters, however not on body fat mass.